ANALISIS PENGELOLAAN BARANG MILIK DAERAH di KABUPATEN MINAHASA UTARA (Studi Kasus Pada Badan Keuangan Kabupaten Minahasa Utara) - Kalangi, Conda Liesye Yolinita Dita; Kalangi, Lintje; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2017)
Management of Regional Property is one of the important indicators in the preparation of financial statements, thus affecting the quality of Local Government Financial Report (LKPD). This study aims to determine the suitability of the management of Regional Property at the Finance Agency of North Minahasa District with the Regulation of the Minister of Home Affairs No. 17 of 2007. This study, the authors use the type of qualitative data from primary and secondary sources. Primary data is taken from place, which is done through obsevarsi and interview. And secondary data, data obtained from the documentation. From the research result shows that the Management of Regional Property in North Minahasa Regency in Budget Year 2015, has been in accordance with the Minister of Home Affairs Regulation No. 17 of 2007, and now has been referring to the Minister of Home Affairs Regulation No. 19 of 2016.Key words : Management of Regional Property.